Efeitos de diferentes densidades populacionais nas estações fria e quente do ano sobre o desempenho de frangos de corte - Goldflus, Fábio; Ariki, Joji [UNESP]; Kronka, Sérgio Do Nascimento [UNESP]; Sakomura, Nilva Kazue [UNESP]; De Moraes, Vera Maria Barbosa [UNESP] (My University, 1997)
The objective of this study was to evaluate the performance of broilers reared under different population densities in the cold and hot seasons of the year. Two identical experiments were conducted, one during the winter for 49 days, and the other during the summer where the chicks were slaughtered at 42 days of age. Commercial Hubbard broiler-type chicks were distributed in a randomized block design in a 4 × 2 factorial arrangement with population densities of 10, 14, 18, and 22 birds/m 2, by sex, and with four replications. Feed intake was reduced with a progressive decrease of available space for the chicks, and it resulted in a linear decrease in weight gain. However, there was a linear increase in the live weight of broilers in kilograms per area of floor space, proportional to the increase of population density, without effect on the viability. The progressive increment in the population density reduced the observed feed/gain ratio during the total winter rearing period for both sexes. There was no effect of population density on this characteristic during the hot season of the year. Population density did not affect the carcass yield of chicks during the summer. However, there was a linear increase on carcass yield with an increase in population density in the winter. The males, at the age slaughtered, had higher weights, feed intakes, and better feed/gain ratios, and lower abdominal fat and higher live weight production in kilograms per floor area than females. However, the viable index for the males was lower. From the results obtained, there was a linear increase in the liveweight of broilers in kilograms per floor area, making it possible to rear broilers under higher population densities, independent of the season of the year, as well as the occurrence of a decrease in feed intake and weight gain of the chicks with a decrease of available space.
Effects of different population densities in the cold and hot seasons of the year on the performance of broilers
Keywords: Broilers; Performance; Population density; Summer season; Winter season; Aves; Gallus gallus